The Role of Vitamin D and the Vitamin D Receptor in Bone Oncology - Horas, K.; Holzapfel, B. M.; Jakob, F.; Kurth, A. A.; Maier, G. (Osteologie, 2018)
Vitamin D deficiency is a global health problem of enormous and increasing dimensions. In the past decades, numerous studies have centered on the role of vitamin D in the pathogenesis and course of many diseases including several types of cancer. Indeed, vitamin D has been widely acknowledged to be involved in the regulation of cell proliferation, differentiation and apoptosis in numerous cancer cells. While the full range of molecular mechanisms involveld in cancer cell growth and progression remains to be elucidated, recent research has deepened our understanding of the processes that may be affected by vitamin D or vitamin D deficiency.In this review, we consider the properties of bone that enable cancer cells to grow and thrive within the skeleton, and the role of vitamin D and the vitamin D receptor in the process of primary and secondary cancer growth in bone.
Keywords: Vitamin D; vitamin D receptor; bone oncology; bone metastases; bone tumour